Pelatihan Sekolah Mandiri Pangan untuk Mendukung Program Makan Bergizi dan Anti Stunting - Meka, Christine Erika; Olviana, Tomycho; Tedju Hinga, Indriati Andolita; Bire Manoe, Lenny Sofia; Kolianan, Jim Brian (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to enhance the capacity of primary schools in developing a School-Based Food Independence Model as a local contribution to the Free Nutritious Meal Program and efforts to accelerate stunting reduction. The program was implemented in Wee Pangali Village, Tambolaka District, Southwest Sumba Regency, involving teachers, students, and parents. The implementation methods included nutrition education, training on transforming school yards into productive food gardens, and simulation of integrating harvests into balanced meal programs for students. The activities also covered nutrition literacy sessions and simple entrepreneurship training based on school production outputs. The results indicate increased participants’ understanding of balanced nutrition and healthy diets, the establishment of school food production units through vegetable gardens and catfish ponds, and strengthened school self-reliance in providing nutritious food ingredients. This program demonstrates that the School-Based Food Independence Model is an effective community-based innovation to improve food security, nutrition literacy, and stunting prevention in rural areas.